VIBRATION-ROTATION SPECTRUM OF THE CARBON-DIOXIDE ACETYLENE VANDERWAALS COMPLEX IN THE 3 MU-REGION - Prichard, D; Nandi, R; Muenter, J; Howard, B (1988)
The infrared absorption spectrum of the carbon dioxide-acetylene van der Waals complex has been observed in a pulsed molecular beam. A color center laser was used to excite the vibration associated with the antisymmetric hydrogen stretching mode of the acetylene monomer. The vibrational origin is 3281.740 cm-1 and the rotational constants are A″ = 8876, B″ = 2959, C ″ = 2155, A ′ = 8864, B ′ = 2855, and C′ = 2154 MHz. The axes of the two monomer are parallel to one another and the complex has C2v symmetry. The separation of the monomer units is 3.285 Å. The angular part of the intermolecular potential function is discussed in terms of electrostatic interactions between distributed multipole moments. © 1988 American Institute of Physics.